2009
DOI: 10.1590/s1806-83242009000300014
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of gingival recession with collagen membrane and DFDBA: a histometric study in dogs

Abstract: In a previous study, we evaluated the findings related to the use of resorbable collagen membranes in humans along with DFDBA (demineralized freeze-dried bone allograft). The aim of this subsequent study was to histometrically evaluate in dogs, the healing response of gingival recessions treated with collagen membrane + DFDBA (Guided Tissue Regeneration, GTR) compared to a coronally positioned flap (CPF). Two types of treatment were randomly carried out in a split-mouth study. Group 1 was considered as test (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…A histometric study in dogs showed that the treatment of the gingival recessions with GTR associated with collagen membrane and DFDBA resulted in larger extension of neoformed cementum and bone, and even in small proportions of residual recessions. 44 Our data demonstrated better results in obtaining a KTW increase with the SCTG procedure (4.5 mm), as our results were higher than those reported by some long-term studies, which showed a range of KTW increase of 1.14 38 , 2.0 and 2.1 11 , 2.5 mm 5 , and 3.7 mm. 7 Such discrepancies among the results of the studies may be related to different methodologies and inclusion criteria, such as classification of gingival recession and differences in values of keratinized tissue width at baseline and the initial recession depth.…”
Section: Discussionsupporting
confidence: 46%
“…A histometric study in dogs showed that the treatment of the gingival recessions with GTR associated with collagen membrane and DFDBA resulted in larger extension of neoformed cementum and bone, and even in small proportions of residual recessions. 44 Our data demonstrated better results in obtaining a KTW increase with the SCTG procedure (4.5 mm), as our results were higher than those reported by some long-term studies, which showed a range of KTW increase of 1.14 38 , 2.0 and 2.1 11 , 2.5 mm 5 , and 3.7 mm. 7 Such discrepancies among the results of the studies may be related to different methodologies and inclusion criteria, such as classification of gingival recession and differences in values of keratinized tissue width at baseline and the initial recession depth.…”
Section: Discussionsupporting
confidence: 46%
“…An excellent model for studying the histological healing pattern after different treatment modalities is the nonhuman primate with contralateral comparable defects . However, as a result of the difficulties in obtaining and housing this type of animal, the canine model is commonly used in Latin American countries . The recognition of a periodontal therapy as a regenerative procedure requires demonstration of new cementum, periodontal ligament, and bone coronal to the base of the defect in human material, and animal studies with appropriate controls and controlled human clinical trials demonstrating significant improvements in clinical attachment and bone levels (Table ).…”
Section: Introductionmentioning
confidence: 67%
“…These materials have been used for many different applications, e.g. to cover buccal gingival areas in Taiwanese dogs 5 or vertical dehiscence bony defects after implantation in patients 14 , for healing of artificial bone defects and buccal recessions in male dogs 22 , to evaluate interproximal infrabony defects in patients 11 , and also to study the reduction of bone resorption in Labrador dogs after insertion of implants 3 .…”
Section: Discussionmentioning
confidence: 99%